Brooke-Spiegler Syndrome: A rare cause of skin appendageal tumor - Suganthan, N; Pirasath, S; Dikowita, DD (Archives of Case Reports, 2018)
A 51-year-old women presented with asymptomatic multiple polypoidal nodules over scalp with simultaneous papularnodular skin eruptions involving nose, nasolabial folds and forehead for 40 years duration. Her daughter also noted to be having multiple papularnodular skin eruptions involving nose, nasolabial folds and forehead which raised curiosity of possible familial condition. The punch biopsy of polypoidal nodule indicating histological evidence of spiradenoma was favour in diagnosis of Brook Spienger Syndrome. We report this case as this is a rare clinical entity.